2012
DOI: 10.1103/physrevlett.109.166802
|View full text |Cite
|
Sign up to set email alerts
|

Topological Surface States with Persistent High Spin Polarization across the Dirac Point inBi2Te2SeandBi2Se2

Abstract: Helical spin textures with the marked spin polarizations of topological surface states have been firstly unveiled by the state-of-the-art spin-and angle-resolved photoemission spectroscopy for two promising topological insulators Bi2Te2Se and Bi2Se2Te. The highly spin-polarized natures are found to be persistent across the Dirac point in both compounds. This novel finding paves a pathway to extending their utilization of topological surface state for future spintronic applications. Three-dimensional topologica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
72
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 43 publications
12
72
1
Order By: Relevance
“…3(b)] using p-polarized light and a photon energy of 52 eV. One can observe the topological surface state with the Dirac point located at a binding energy of about 0.28-0.33 eV which is comparable to the one obtained for Bi 2 Se 2 Te and Bi 2 Te 2 Se compounds [20]. Similarly, in Ref.…”
Section: Electronic and Spin Structuresupporting
confidence: 73%
See 2 more Smart Citations
“…3(b)] using p-polarized light and a photon energy of 52 eV. One can observe the topological surface state with the Dirac point located at a binding energy of about 0.28-0.33 eV which is comparable to the one obtained for Bi 2 Se 2 Te and Bi 2 Te 2 Se compounds [20]. Similarly, in Ref.…”
Section: Electronic and Spin Structuresupporting
confidence: 73%
“…Some of these compounds possess extraordinary wide fundamental energy gaps and nearly ideal Dirac cones [8,15]. It was also shown that the modification of such features of the electronic structure as the position of the Dirac point relative to the Fermi level and to the bulk valence band edge, the absence of bulk conduction band states at the Fermi level, etc., can be efficiently controlled by means of a variation of the third component concentration [1,[5][6][7]9,20] or by diluted metal atom doping [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] The controlled removal of excess electrons was achieved by Sn doping and Bi excess in Bi 2 Te 2 Se. 15 Bi 2 Se 2 Te was theoretically predicted as a topological insulator 16 and recent experiments have shown the characteristic topological features in the band structure and in transport measurements 17,18 In these experimental studies, the Fermi energy was located in the bulk band gap, well above the Dirac point, implying negative charge carriers (electrons) confirmed by Hall measurements. In this study, we have observed quantum oscillations from the topological surface states of p-type single crystals of Bi 2 Se 2.1 Te 0.9 despite their bulk metallic temperature dependence.…”
mentioning
confidence: 93%
“…Bi 2 (Te 1−x Se x ) 3 compounds, originally employed for thermoelectric devices due to their large Seebeck constant 5 , belong to this category, thanks to the large spin orbit coupling due to heavy bismuth atoms. The linearly dispersing surface states have been observed by angle resolved photoemission (ARPES) 3,[6][7][8][9] . Samples are usually of ntype with the Fermi level located in the conduction band because of the antisite doping related to Se vacancies 10 .…”
Section: Introductionmentioning
confidence: 99%